MAKESPAN MINIMIZATION ON A SINGLE BATCH PROCESSING MACHINE WITH UNEQUAL JOB READY TIMES - Velez-Gallego, Mario C; Damodaran, Purushothaman; Rodríguez, Manuel (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
A batch processing machine (BPM) can process several jobs simultaneously as a batch as long as its capacity is not violated. The processing time of each job, their ready times and sizes are given. This research was motivated by a practical application observed at an electronics manufacturing facility where a BPM is a bottleneck and consequently minimizing the makespan is the primary objective. The batch processing time is the largest processing time among the jobs in the batch, and the batch ready time is the largest ready time among the jobs in the batch. Given that the problem is NP-hard we propose a constructive heuristic to solve the problem under the assumptions of non-identical job sizes and non-zero job ready times. The computational experiments conducted on a set of randomly generated problem instances show that the proposed approach outperforms other approaches available in the literature at a reasonable computational cost.